Entrepreneurship Values and Passion as Life Skills in Buddhist Students in West Kalimantan Province - Edi Susanto; Lianah The; Mettadewi Wong (Universitas Muhammadiyah Enrekang, 2025)
This research aims to understand how Buddhist students at SMK N 3 Pontianak interpret and implement entrepreneurship and passion as life skills. Using Miles and Huberman's qualitative approach and interactive analysis, this research found that entrepreneurship helps students develop life skills such as the ability to innovate, create opportunities, manage risks, and contribute socially. Passion encourages perseverance, creativity and the ability to face challenges. Buddhist values ​​such as the Four Noble Truths, Samma Ajiva, and Samma Vayama provide ethical guidance, shaping into students individuals who are balanced, responsible, and ready to face the world of work or entrepreneurship.